INVESTIGATION OF WAITING TIME FOR PATIENT TRANSFER FROM EMERGENCY ROOM TO INPATIENT WARD AT DR. ETTY ASHARTO HOSPITAL BATU CITY - bagus sadewo, ageng; Holipah; Irawan, Rachmad Ari (Journal of Community Health and Preventive Medicine, 2025)
The emergency department is a critical service in hospitals. The duration of patient waiting time in the emergency unit is a sensitive matter, as it can affect the patient's condition and serves as an indicator of hospital service quality. This study aims to determine the length of waiting time in the Emergency Unit (ER) and the issues related to the delay in transferring patients from the ER to inpatient care.This research uses a time and motion study method, conducted by following and recording the time starting from the patient's arrival at the ER until their transfer to the inpatient ward. Data were collected across various work shifts and different days, with a total of 21 samples.The results of this study show that waiting times ranged from 1 to 10 hours. The high volume of patients planning for inpatient care during the morning and afternoon shifts—coming from both the polyclinic and the ER—creates service bottlenecks. Additionally, supporting examinations from the polyclinic often overlap with those from the emergency unit.The findings of this study can help hospital management identify service obstacles, and further analysis is needed to address the problems related to patient transfer time from the ER to inpatient care, as this directly impacts the quality of service.